1999
DOI: 10.1038/sj.onc.1202794
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane protein tyrosine phosphatase RPTPσ modulates signaling of the epidermal growth factor receptor in A431 cells

Abstract: Attenuation of epidermal growth factor receptor signaling by the ganglioside G M3 has previously been found to involve activation of an unknown protein-tyrosine phosphatase (PTP). In transient expression experiments we tested dierent PTPs for activation towards EGF receptor by G M3 . The transmembrane PTP RPTPs but not RPTPa or the SH2-domain PTP SHP-1 exhibited elevated activity towards EGF receptor in G M3 -treated cells. The possible relevance of RPTPs for regulation of EGF receptor signaling activity was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…This observation further supports the concept that EGFR is acted upon by multiple RPTPs. In this regard, both RPTP LAR, and RPTP-have been shown to reduce EGFR phosphorylation (18,23). However, whether either RPTP acts directly on EGFR, or which phosphotyrosine residue(s) either RPTP affects remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This observation further supports the concept that EGFR is acted upon by multiple RPTPs. In this regard, both RPTP LAR, and RPTP-have been shown to reduce EGFR phosphorylation (18,23). However, whether either RPTP acts directly on EGFR, or which phosphotyrosine residue(s) either RPTP affects remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, focal somatic alteration of this gene has not been described in human disease. PTPRS has been shown to directly interact with and dephosphorylate EGFR (34,35). We observed deletions in this gene that were highly focal, robustly identifying PTPRS as the target of CNA on chromosome 19p13.3, a genomic region frequently lost in several cancers and thought to harbor an as-yet-unidentified tumor suppressor (36)(37)(38)(39).…”
Section: Protein Tyrosine Phosphatase Receptor S (Ptprs) Is Frequentlymentioning
confidence: 99%
“…Alterations of PTPRS in cancer are poorly described, and no focal alterations of this gene have been documented. Biochemical experiments have demonstrated that PTPRS directly interacts with EGFR and dephosphorylates and inactivates EGFR and loss of PTPRS enhances EGFR-induced transformation (34,35). The microdeletions in PTPRS result in loss of mRNA expression (Fig.…”
Section: Protein Tyrosine Phosphatase Receptor S (Ptprs) Is Frequentlymentioning
confidence: 99%
“…Pestana et al 31 reported that EGF receptor dephosphorylation was activated by GM3 and that this event was mediated by the activation of receptor-type protein tyrosine phosphatase by GM3. Hence, GD1a is likely to activate the protein tyrosine phosphatases (hypothesis iv).…”
Section: Level Of C-met Tyrosine Phosphorylation In Gd1a-pretreated Hmentioning
confidence: 99%